Temperature distribution and heat losses in molten salts tanks for CSP plants. (October 2016) - Prieto, Cristina; Miró, Laia; Peiró, Gerard; Oró, Eduard; Gil, Antoni; Cabeza, Luisa F.
Highlights: The two-tanks molten salts storage system with "solar salt" is studied. Experimental evaluation of temperature distribution and heat losses in the tanks. Temperature is lower at the external part of the tank and no stratification is seen. Influencing parameters are identified. Measured heat losses were from 61 W/m 2 (bottom) to 80 W/m 2 (walls). Abstract: Solar power plants have been deployed in the last 20 years, so the interest in evaluating their performance is growing more and more. In these facilities, thermal energy storage is used to increase dispatchability of power. The two-tank molten salts storage system with "solar salt" (60 wt.% NaNO3 and 40 wt.% KNO3 ) is the one commercially used today. To be able to achieve a deep understanding of the two-tank solar storage systems with molten salts, in 2008 a pilot plant was built at the University of Lleida (Spain) and the experimental evaluation of the temperature distribution inside the tanks and their heat losses are presented in this paper. Therefore, this pilot plant is equipped with several temperature sensors inside the tank as well as in the different layers of external insulation. As expected, temperature is lower at the external part of the tank (near the cover, at the bottom and near the walls) and no stratification is seen. It is found that the influencing parameters in the temperature distribution of the salts inside the tank are: insulation, and the existence of different electrical resistances and the orientation and surroundings of the tank. Heat losses were measured and compared both with a simulated 1-D steady state model and previous literature. Measured heat losses were from 61 W/m 2 through the bottom to 80 W/m 2 through the walls (with 73 W/m 2 through the cover).